Peran Self-Efficacy terhadap Perilaku Kerja Inovatif pada Karyawan Industri Manufaktur: Studi Kasus pada PT Polytama Propindo: Indonesia - Khairunnisa, St Nabilah; Nurmala, Sukma (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Brawijaya, 2023)
This research aims to determine the role of self-efficacy in innovative work behavior among employees of PT Polytama Propindo, a manufacturing industry. The respondents in this study consist of 105 permanent employees of PT Polytama Propindo who have been working for at least one year and are aged between 25 and 65 years old. This is a quantitative research with two measurement instruments adapted into Indonesian: the General Self-Efficacy (GSE) scale to measure self-efficacy and the Individual Innovative Work Behavior (IWB) scale to measure innovative work behavior. The data analysis technique used is simple linear regression. The results of this study show that self-efficacy plays a significant role in innovative work behavior (R2Â = 0.291, Sig. = 0.000). This indicates that self-efficacy accounts for 29.1% of the variance in employee's innovative work behavior. The findings of this research are expected to contribute to the existing literature on innovative work behavior among employees and serve as a reference for companies to enhance their employee's self-efficacy. Keywords: Employee, Innovative, Work Behavior, Manufacturing Industry; Self-Efficacy